Primary central nervous system diffuse large B-cell lymphoma: a report on unusual presentation with acute onset diplopia and proptosis - Pokhrel, Bibesh; Thapa, Amit (Nepal Journal of Neuroscience, 2020)
Acute onset of diplopia with proptosis in case of primary CNS lymphoma has not been reported yet in the literature. Blurred vision, reduced vision, and floaters are the commonest reported presentations. We report a case of a 41-year-old HIV positive male who presented with diplopia in left eye for two weeks with proptosis of left eyeball. CT Scan study of head and orbit showed heterogeneously enhancing large soft tissue calcified orbital mass pushing the left eyeball out of orbit. Right fronto-temporo-orbito-zygomatic (FTOZ) osteoplastic craniotomy with gross total excision of tumor was performed. Histopathological evaluation was suggestive of Non-Hodgkins Lymphoma. Immunohistochemistry confirmed the diagnosis of diffuse large B-cell lymphoma, non-germinal center type. Five months follow-up showed good recovery with no evidence of recurrence.